Focal atrial tachycardia. Issue 3 (13th May 2009) - Rosso, Raphael; Kistler, Peter M
Abstract : Focal atrial tachycardia is a relatively uncommon arrhythmia. Nevertheless, the management of highly symptomatic patients with focal atrial tachycardia can be problematic owing to the poor response to medical treatment. Moreover, focal atrial tachycardia can trigger other atrial arrhythmias like atrial fibrillation and flutter. Radiofrequency ablation of focal atrial tachycardia is extremely successful and this approach is becoming the preferred treatment for symptomatic patients.In this review, we describe the pathophysiology, anatomical localisation, clinical features, diagnosis and therapeutic options for the management of focal atrial tachycardia.